THE EFFECT OF COMPLEX STRENGTH TRAINING ON EXPLOSIVE POWER AND SPEED STRENGTH OF BOXERS UNDER 20 YEARS OF AGE - KADHIM , AHMED QASIM (International Journal of Advance Research in Education & Literature (ISSN 2208-2441), 2025)
Muscular capabilities are among the fundamental pillars upon which skill performance in boxing depends, particularly explosive power and speed strength, due to their crucial role in executing offensive and defensive combat skills during a fight. From this perspective, the research problem arose regarding the limited effectiveness of traditional training methods in developing these capabilities among juniors. This necessitated the search for more modern and effective training alternatives that keep pace with the demands of high performance in boxing.Accordingly, this study aimed to develop a physical training curriculum based on the principle of strength complexity, a contemporary training method that combines weight training, plyometric exercises, and jumping exercises. The goal is to stimulate the neuromuscular system and achieve a high physiological response that contributes to the development of players' physical and skill performance. The researcher sought to measure the impact of this approach on developing explosive power and speed arm strength among Al-Hilla Club boxing players under the age of twenty. Based on the study's objective, the researcher formulated his main hypothesis, which states that there is a positive effect of physical training based on the principle of strength complexity on developing explosive power and speed strength in young boxers, with statistically significant differences between the results of the pre- and post-tests in favor of the post-test.To achieve the study's objectives, the researcher used the experimental method with a single-group design with pre- and post-measurements, as it suited the nature and requirements of the study. The research sample included (6) players randomly selected from a research population of (9) boxers, while the other three were assigned to the exploratory experiment. The training program was implemented over a period of eight weeks, with three training sessions per week. Modern sports training principles were used in terms of intensity, volume, repetition, and rest, commensurate with the players' abilities.Measurement tools relied on standardized field tests to assess the explosive power of the arms (throwing a medicine ball) and speed strength (lowering and raising the medicine ball within a specified time), supported by the use of technological means to ensure accuracy and reliability in performance and measurement. The importance of the study lies in its endeavor to provide a modern applied vision that contributes to the development of the physical abilities that influence the skill performance of junior boxers. This is achieved by employing advanced scientific training methods that keep pace with the requirements of high-performance sports. It also aims to enrich the training content of coaches and specialists with scientific material that can be applied practically.The researcher concluded that exercises based on the principle of force complexity are an effective training tool for developing explosive power and speed arm strength. They significantly improved aspects of physical performance associated with skill performance among the sample. The researcher recommends adopting the force complexity approach within training programs directed at boxers, given its positive impact on developing muscular motor abilities. He emphasized the importance of focusing on developing explosive power as one of the critical variables in improving physical and skill performance in boxing.